MENINGKATKAN PENGUASAAN BELAJAR IPS MELALUI STRATEGI EKSPOSITORI SISWA KELAS VI SDN 01 TANJUANG BALIK KECAMATAN PANGKALAN KOTO BARU KABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Tuti Erita (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the low of IPS student learning mastery of class VI SDN 01 Tanjuang BalikDistrict of Lima Puluh City West Sumatra. The objectives to be achieved in this research is to improve themastery of IPS learning on the material development of the territory of Indonesia Student Class VI SDN 01Tanjuang Balik District of Lima Puluh Kota West Sumatera through Expository strategy implemented for 1month. This research was conducted at SDN 01 Tanjuang Balik District of Lima Puluh Kota Sumatera Barat.The researcher's first grade is Class VI semester one with a total of 27 students. This classroom action researchbegan to take place in early August 2016. This form of research is a classroom action research. The instrumentof this research consists of instrument of activity sheet of teacher and student and test result of learning. Basedon the results of the analysis and discussion as presented in chapter IV, it can be concluded that the applicationof learning method using expository strategy can increase the IPS learning mastery in the material developmentof Indonesian territory of grade VI student SDN 01 Tanjuang Balik Pangkalan Koto Baru Sub-district, LimaPuluh Kota, West Sumatera. This success is caused by the application of learning methods using studentexpository strategies become more active which means students tend to be positive in following the teaching andlearning process provided by the teacher. Through the improvement of learning by using expository strategy incycle II, student learning outcomes reach individual completeness and mastery of class with average value 74,1.